Oral Message Reception at the Early School Age - Ludmila ARMAȘU-CANȚÎR; Liliana SCÎNTEI (ACROSS, 2022)
The competence to receive the oral message is the first general competence in the National Curriculum for the mother tongue. The curricula in the fundamental acquisitions cycle require clarifications from a methodical point of view, both in Romania and in Moldova, regarding the contents and learning activities that will ensure the development of this competence. At a young age, the ability to receive the written message is poorly developed. That is why we highlight the role of listening in the development of vocabulary, in learning the communicative functions of the language and in creating the premises for the formation of written skills. Listening activities of the literary text require working strategies based on active listening and comprehension of the listened text.